LITERARY AND NONLITERARY FORMS OF SPEECH IN ENGLISH AND UZBEK ("Conference on Universal Science Research 2023", 2023)
In both English and Uzbek languages, there are literary and nonliterary forms of speech. This article gives  some information about each.